CHANGES IN BLOOD GLUCOSE LEVELS IN EXPERIMENTAL ANIMALS WITH HYPERGLYCEMIA DUE TO LIME (Citrus aurantifolia Swingle) PEEL EXTRACT - Rivan Virlando Suryadinata; Kezia Sefania; Heru Wijono (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
Chronically elevated levels of glucose in the blood can lead to various complications. As a result, it can accelerate the damage to various organ tissues in the body. Several measures are needed to maintain the stability of normal blood glucose levels to prevent tissue damage, as well as providing additional intake such as lime peel extract which is believed to have high flavonoid content in lowering blood glucose levels. For this reason, this study aimed to analyse changes in blood glucose levels by giving lime extract to alloxan-induced experimental animals. This study uses an experimental post-test control group design. The results showed increased in blood glucose levels in the positive control group (p < 0.005). In addition, the lime (Citrus aurantifolia Swingle) peel extract treatment group showed changes in blood glucose levels (p < 0.005). It was concluded that increasing the intake of lime peel extract can reduce blood glucose levels. Peningkatan kadar glukosa dalam darah secara kronis dapat menyebabkan berbagai komplikasi. Akibatnya, dapat mempercepat kerusakan berbagai jaringan organ dalam tubuh. Beberapa tindakan diperlukan untuk menjaga stabilitas kadar glukosa darah normal untuk mencegah kerusakan jaringan. Serta memberikan asupan tambahan seperti ekstrak kulit jeruk nipis yang dianggap memiliki kandungan flavonoid yang tinggi dalam menurunkan kadar glukosa darah. Untuk itu, penelitian ini bertujuan untuk menganalisis perubahan kadar glukosa darah dengan pemberian ekstrak jeruk nipis pada hewan coba yang diinduksi aloksan. Penelitian ini menggunakan rancangan eksperimen post-test control group design. Hasil penelitian menunjukkan adanya peningkatan kadar glukosa darah pada kelompok kontrol positif (p < 0,005). Selain itu, kelompok perlakuan ekstrak kulit jeruk nipis (Citrus aurantifolia Swingle) menunjukkan perubahan kadar glukosa darah (p < 0,005). Oleh karena itu, dapat disimpulkan bahwa peningkatan asupan ekstrak kulit jeruk nipis dapat menurunkan kadar glukosa darah.